Generación de un geoportal con análisis espacial aplicando operaciones geométricas - Torre Gordón, Nelson David de la (2017)
The present project seeks to apply the acquired knowledge for the construction of a GeoPortal that allows basic geometric operations with spatial data stored in any previously loaded database. Selection of information is dynamic, allowing to assemble queries so finally encoded in GeoJSON format that can be copied or transmitted to another system in a light and fast way. In the first chapter is the theoretical framework necessary for understanding the construction of the GeoPortal. In the second chapter an analysis of available information is carried out and can be reused for the construction of the GeoPortal, next proceeding to the design of screens that allow to successfully finish the stated objective. Chapter three details the steps taken to obtain the GeoPortal, from the reverse engineering applied to previous projects to the implementation of new functionalities and obtaining results.